Assessing the supply chain effect of natural disasters: Evidence from Chinese manufacturers - Katharina Längle; Ankai Xu; Ruijie Tian (World Trade Organization (WTO), 2021)
This paper uses Chinese firm level data to detect the international propagation of adverse shocks triggered by the US hurricane season in 2005. We provide evidence that Chinese processing manufacturers with tight trade linkages to the United States reduced their intermediate imports from the United States between July and October 2005. We further show that the direct exposure to US supply shocks led to a temporary decline of firm exports between September and November 2005, although we do not find consistent evidence of international propagation of supply shocks along global value chains. Moreover, the paper finds that firms with more diversified suppliers tend to be less affected by the US hurricane disaster, pointing to firm sourcing diversification as a way to increase resilience to adverse shocks.
Keywords: F12; F14; F15; F61; D5; L14; E23; 330; production networks; resilience; diversification; shock transmission; supply chains; natural disasters